Nuove ipotesi su produzione e circolazione della ceramica comune d’età romana nell’attuale Canton Ticino (Svizzera) - De Micheli Schulthess, Christiane (Rei Cretariae Romanae Fautorum Acta, 2023)
The presence of clay deposits in Canton Ticino favoured the establishment of quarries and kilns from the Middle Ages until the beginning of the 20th century. Their organisation was centred on several local production centres, run by small groups of craftsmen and not always active. However the distribution of their products was widespread. This production framework could also be applied to the Roman period, for which archaeological data on centres of production or laboratory analyses to determine the origin of the materials are currently lacking. The analysis of olpai, bowls and jars, whose association in the funerary contexts of the region is attested for the different periods, indicating an important presence of variants within a rather circumscribed territory during the 1st century AD. This variety is drastically reduced in the following century in the case of the olpai, while for bowls and jars there is a certain continuity. One can therefore suppose different reasons for the morphological choice of the vessels.